Peran dan Kompetensi Muthawif pada Kepuasan Layanan Jamaah Umrah pada PT. Amanah Safari Internasional (Asafi) Tour Bengkulu - Hellannisa Alfidah; Yosy Arisandi; Makmur (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the role and competence of muthawif in relation to the satisfaction of Umrah pilgrims’ services at PT. Amanah Safari Internasional (ASAFI) Tour Bengkulu. The focus of this study includespilgrims’ experiences related to the role of the muthawif during theimplementation of Umrah,pilgrims’ perceptions of the muthawif competence, and the influence of these roles and competencies on pilgrims’ satisfaction, both emptionally and spiritually. This study employs a qualitative approach with a descriptive method. Data collection techniques include interviews, observation, and documentation. The results of the study indicate that, in general, pilgrims have a positive impression of the role of the muthawif. The muthawif is considered capable of providing clear, structured, and easily understood guidance in worship, as well as assisting pilgrims throughout the Umrah rituals in the Holy Land.In addition, the competence of the muhawif is considered good, as reflected in their mastery of Umrah materials, effective communication skills, and ability to handle various characteristics of pilgrims.The roles and competencies have been proven to significantly contribute to the level of pilgrims’ satisfaction, both in terms of service quality and the spiritual experience gained during the Umrah pilgrimage.